An Overview of Shape Memory Alloy-Coupled Actuators and Robots - Rodrigue, Hugo; Wang, Wei; Han, Min-Woo; Kim, Thomas J Y; Ahn, Sung-Hoon (Soft robotics, 2017)
The one-dimensional deformation of shape memory alloy (SMA) wires and springs can be implemented into different types of functional structures with three-dimensional deformations. These structures can be classified based on the type of structure and how the SMA element has been implemented into the following categories: rigid mechanical joints, semi-rigid flexural hinges, SMA elements externally attached to a soft structure, and embedded into the soft structure. These structures have a wide range of properties and implementation requirements, and they have been used to produce a variety of robots with rigid and soft motions. The different research efforts to develop actuators and robots related to each type of structure are presented along with their respective strengths and weaknesses. A model is then developed to discuss the performance and applicability of SMA wires versus SMA springs for actuators with a polymeric matrix to see the effect of each type of SMA on the selection of design parameters. A comparison of the different types of structures and the applicability of different types of SMA elements for different types of structures is then presented.